Effects of Reflection to Improve Goal-Directed Self-Talk on Endurance Performance - Alexander T. Latinjak; Bernat de las Heras; Arnau Sacot; David Fernandez; Daniel Robinson; Andrew M. Lane (MDPI AG, 2018)
We investigated the effects of an intervention that encouraged reflection on organic self-talk used during endurance performance. Using an experimental design, we compared the effects of enhancing metacognitive skills by (a) planning and (b) reviewing and evaluating goal-directed self-talk. Participants completed three time-to-exhaustion cycling task trials in which we hypothesized that the intervention group would perform significantly better than the control group. Further, we expected a reduction in perceived exertion for a given workload among participants following a self-talk intervention. Thirty-four participants completed a time-to-exhaustion cycle ergometer test, after which participants were randomly divided into an intervention and control group. The intervention group performed reflection tasks on performance in the time-to-exhaustion test. Participants completed two further time-to-exhaustion tests. Repeated measures analyses of covariance to test whether the intervention group performed for longer indicated no significant difference in time to exhaustion (p = 0.157). Perceived exertion rates were 2.42% higher in the intervention compared to the control group (p = 0.025). In conclusion, in the intervention group, goal-directed self-talk led to increased sensitisation to perceived exertion, and participants chose to stop exercising at this point rather than repeat implementation of self-talk statements and persist for longer.